2002
DOI: 10.1292/jvms.64.677
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Augments GLUT4 Expression and Insulin-Sensitive Glucose Transport System in Differentiating Rat Brown Adipocytes in Culture.

Abstract: ABSTRACT. The effects of triiodothyronine (T3) on differentiation-dependent expression of GLUT and responses of glucose transport to insulin and norepinephrine (NE) were investigated. Precursor cells of brown adipocytes isolated from the interscapular brown adipose tissue of newborn rats were cultured in the absence or presence of various concentrations of T3. Western bolt analysis revealed that treatment with T3 resulted in an increased expression of GLUT4, in a dose-dependent manner, whereas GLUT1 contents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Those factors responsible for the high-fat diet induced GLUT4 repression could be arachidonic acids (24,25) or other long chain fatty acids, such as stearic acids, oleic acids, etc (25). Thyroid hormone treatment of rats caused an increase in GLUT4 mRNA and protein level in muscle (26,27) and adipocytes (28).…”
Section: Metabolic and Hormonal Control Of Glut4 In Muscle And Adiposmentioning
confidence: 97%
“…Those factors responsible for the high-fat diet induced GLUT4 repression could be arachidonic acids (24,25) or other long chain fatty acids, such as stearic acids, oleic acids, etc (25). Thyroid hormone treatment of rats caused an increase in GLUT4 mRNA and protein level in muscle (26,27) and adipocytes (28).…”
Section: Metabolic and Hormonal Control Of Glut4 In Muscle And Adiposmentioning
confidence: 97%
“…We demonstrated that T 3 replacement can completely recover the impaired glucose tolerance in grt mice, and that the plasma levels of insulin in response to a glucose load were only slightly increased in T 3 -treated grt mice, indicating that hypothyroidism is associated with a deterioration of glucose metabolism. The recovery of impaired blood glucose levels in T 3 -treated grt mice may be associated with increased GLUT4 localized in the myocytes and adipocytes that is involved in glucose transport, since GLUT4 protein expression is regulated by T 3 (Shimizu & Shimazu 2002). It has been reported that although subjects with hypothyroidism are characterized by attenuated plasma insulin concentrations and increased glucagon concentrations in the basal state, T 4 replacement can, among other effects, result in partial amelioration of insulin secretion and improved insulin sensitivity (Handisurya et al 2008).…”
Section: Tpst2mentioning
confidence: 99%
“…Increase in both hepatic insulin resistance (11,12) and insulin-mediated glucose uptake is observed in hyperthyroidism as compared with euthyroid conditions (11). Thyroid hormones influence insulin action in skeletal muscle and adipose tissue in part by upregulating the expression of the muscle/fat-specific glucose transporter 4 (13,14). In contrast, studies in hypothyroid conditions show a decrease in both hepatic insulin resistance (12) and insulin-mediated glucose uptake in muscles (10,12).…”
Section: Introductionmentioning
confidence: 99%